Perancangan aplikasi augmented reality perangkat keras komputer bagi siswa sekolah dasar - Meinardi Trianto, Edwin; John Pattiasina, Timothy; Purnomo Urip, Felipe; Rahmawati, Titasari; Sena, I Gede Wiarta; Soedargo, David Saputra Octadianto (Computer Science and Information Technology, 2023)
Augmented Reality is a system or form of technological progress and has been used in several things in life. The application of Augmented Reality as a media to support work and learning has been widely used. The use of Augmented Reality technology as a learning medium can support visualization in the field of elementary school education, especially in information and communication technology lessons or what is often known as ICT subjects. The application, called "Augmented Reality Information and Communication Technology" (ARTIK), was developed with the aim of attracting elementary school students' interest in supporting ICT learning, especially understanding computer hardware. This game application was created using the Unity 3D tool and using the Android operating system on a smartphone, as well as utilizing the Vuforia library as an Augmented Reality implementation module. The testing method used is the black box testing method, where the ARTIK application can display 3-dimensional objects on the smartphone well and clearly. Apart from that, ARTIK also has a learning feature with animation and a quiz module to assess how well the learning material is absorbed. The ARTIK learning educational application can be used by elementary school students as a support for learning ICT courses to better understand what hardware looks like using Augmented Reality technology.